HASIL BELAJAR KETERAMPILAN PROSES FISIKA SISWA MELALUI PENDEKATAN KONTEKSTUAL DI KELAS X SMA N 1 PANGKALAN LESUNG - Azizahwati Azizahwati; Ratih Permatasari; Hendar Sudrajad (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2009)
The purpose of this research has described learning result of physics science skill process byapplying kontextual learning. The subject of this research is 25 students of SMAN 1 PangkalanLesung. Data is collected by giving the applicative process test after finishing the subject. Dataanalysis showed that abortive power is with good category, learning effectiveness can becaregorized in effective, but completeness of students learns is not complete. So, the kontextuallearning is clafified effective for science process skill achievment of second year students at SMAN1 Pangkalan Lesung.